Article Review the Potential of Banana Stems as a Source of Prebiotic - Ni Made Ayu Suardani Singapurwa; Ni Wayan Nursini; Purwaningtyas Kusumaningsih; I Putu Candra; A.A. Made Semariyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
A Prebiotic is a food that cannot be digested by the human body but provides health benefits by increasing the growth or activity of good bacteria in the large intestine. Prebiotics are indigestible foodstuffs that selectively stimulate the growth and/or activity of beneficial bacteria in the colon, improving health and well-being. Prebiotics can be found in high-fibre foods such as whole grains, bananas, leafy greens, onions, garlic, and soybeans. Bananas are one potential source of prebiotics because they contain dietary fibre compounds that can stimulate the growth of good bacteria in the large intestine. Banana stems contain dietary fibre compounds that can stimulate the growth of good bacteria in the large intestine, so it has the potential as a source of prebiotics. Prebiotic flour can be prepared from banana stems by identifying the genotype of amylolytic bacteria